An evaluation of quality of life of skin cancer patients after surgery using dermatology life quality index tool - Jain, Shailendra Kumar; Jain, Preeti; Singh, Abhishek; Goel, Shewtank; Goyal, Pooja; Tank, Rakesh (International Journal of Research in Medical Sciences, 2017)
Background: Quality of life (QOL) has been identified as an important outcome in cancer researches yet the most common malignancy among humans, non-melanoma skin cancer (NMSC), but poorly studied. Aim of the study was to analyze the quality of life of non-melanoma skin cancer patients after surgery using dermatology life quality index inventory (DLQI). Methods: Retrospective cohort of patients operated for non-melanoma skin cancer in last 2 years and paid postoperative 4-month visit formed the study population. Inclusion criteria consisted of subjects operated for non-melanoma skin cancer and paid follow up visits having sufficient physical and mental capacity. Fifty-six subjects fulfilled the selection criteria laid down thus included in this study. Study tools were records of patients, which were obtained from medical records section. If any more information was required, study subjects were contacted. Results: Out of total 56 study subjects, Basal cell carcinomas were found in 91.1% (n=51); squamous cell carcinomas were detected in 7.2% (n=4). Single location wise more lesions were located on the nose 22.1% (n=15) and forehead 17.6% (12). For most patients (75%), the lesion had not been previously treated. 58.9% subjects did not have any other associated co-morbid condition. Lower mean values were observed post-operative i.e. lower DLQI scores were recorded 4 months after surgery in our study which indicates that adverse effects were not very prominent thus preserving quality of life post operatively. Paired sample t-tests revealed a significant effect on DLQI item 1 (p=0.008), item 2 (p=0.043), and item 4 (p=0.003), with scores decreasing (improving QOL) after treatment. The change in total DLQI score demonstrated a trend toward significance, with overall QOL improving after treatment (p=0.024). Conclusions: Previously commonly employed dermatological Quality of life tools demonstrated minimal handicap at initial diagnosis and little change after treatment of nonmelanoma skin cancer. Development of disease-specific instrument is warranted to explore the disease process.